"Digital Colonization" of Highly Regulated Industries: An Analysis of Big Tech Platforms' Entry into Health Care and Education. (August 2022) - Ozalp, Hakan; Ozcan, Pinar; Dinckol, Dize; Zachariadis, Markos; Gawer, Annabelle
Digital platforms have disrupted many sectors but have not yet visibly transformed highly regulated industries. This study of Big Tech entry in healthcare and education explores how platforms have begun to enter highly regulated industries systematically and effectively. It presents a four-stage process model of platform entry, which we term as "digital colonization." This involves provision of data infrastructure services to regulated incumbents; data capture in the highly regulated industry; provision of data-driven insights; and design and commercialization of new products and services. The article clarifies platforms' sources of competitive advantage in highly regulated industries and concludes with managerial and policy recommendations.